Horizontal rectus muscle insertion sites in patients with infantile esotropia and acute acquired concomitant esotropia - Shuyuan Liao; Yun Wen; Qingqing Ye; Linxing Chen; Tao Shen (Heliyon)
Purpose: To investigate the characteristics of horizontal rectus muscle insertion sites in patients with infantile esotropia (IE) and acute acquired concomitant esotropia (AACE). Methods: The medical records of 166 IE patients and 261 AACE patients who underwent horizontal rectus muscle surgeries were reviewed retrospectively, including age at surgery, spherical equivalent (SE), and angle of esodeviation at near and distance. The limbus-insertion distances (LID) and widths of the medial rectus (MR) and lateral rectus (LR) muscles were measured intraoperatively using a caliper. The insertion parameters and clinical features were compared between different ages and types of esotropia, and a correlation analysis was performed between these variables. Results: In IE patients under 12 years old, the MR LID was positively correlated with age, whereas the LR LID was negatively correlated with the angle of esodeviation at distance. In IE patients over 12 years old, the LR width was negatively correlated with the angle of esodeviation at near. In AACE patients, the MR LID was negatively correlated with the angle of esodeviation at distance, whereas the LR width was negatively correlated with the SE. Conclusions: The LID and width of the horizontal rectus muscle insertions were not significantly different in age-matched patients with IE and AACE. In IE patients, the LR insertion parameters were correlated with the angle of esodeviation, but in AACE patients, the MR LID was correlated with the angle of esodeviation. The clinical significance of these findings still needs to be investigated further.